Associations Between Social Support, Health Belief Model Constructs, and Smoking Cessation Among Patients Attending a Smoking Cessation Clinic in Surakarta, Central Java, Indonesia - Seindy Arya Kusuma Timoer; Hendrastutik Apriningsih; Bhisma Murti; Jatu Aphridasari; Ana Rima Setijadi (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Smoking behaviour is a major health problem in Indonesia, with a high prevalence rate. The decision to quit smoking is influenced by various factors, including social support and components of the Health Belief Model (HBM). However, the direct and indirect mechanisms through which social support and HBM components influence smoking behaviour remain incompletely understood, particularly among patients attending smoking cessation clinics. Understanding these factors is crucial for improving the success of smoking cessation programmes. Subjects and Method: This analytical observational study employed a case-control design involving patients at the Surakarta Smoking Cessation Clinic from September 2025 to November 2025. Data were collected using structured questionnaires and analysed using logistic regression and generalized structural equation modeling (GSEM) to evaluate the direct and indirect effects between variables. Results: Self-efficacy had a positive effect on smoking cessation (b = 1.23; 95% CI = 0.60 to 1.85; p < 0.001). Perceived susceptibility (b = 0.66; 95% CI = 0.05 to 1.27; p = 0.034) and perceived benefit (b = 0.63; 95% CI = 0.001 to 1.26; p = 0.050) have a positive effect on smoking cessation, whilst perceived barriers have a negative effect on smoking cessation (b = −0.70; 95% CI = −1.30 to −0.09; p = 0.025). Cues to action had a positive effect on self-efficacy (b = 0.73; 95% CI = 0.16 to 1.31; p = 0.013). Social support positively influenced cues to action (b = 1.85; 95% CI = 1.21 to 2.49; p < 0.001) and perceived benefits (b = 1.00; 95% CI = 0.42 to 1.59; p = 0.001). Social support influences smoking cessation indirectly through cues to action, perceived benefits, and self-efficacy. Conclusion: Smoking cessation is influenced by the interaction between social support and the components of the Health Belief Model, with self-efficacy being the most dominant factor. Social support plays an indirect role by increasing cues to action, perceived benefits, and self-efficacy; therefore, strengthening these factors is important in improving the success of smoking cessation.